Making conversation in modernist fiction - Alsop, Elizabeth (Columbus : The Ohio State University Press, 2019)
"Analyzes the function of dialogue in early twentieth-century novels and discusses works by Henry James, James Joyce, Ernest Hemingway, William Faulkner, Virginia Woolf, and Gertrude Stein"--
Dialogue and its discontents -- The consensual voice: fantasies of reciprocity in James and Hemingway -- The exceptional voice: Joyce, Faulkner, and the dream of autonomy -- The paradoxical voice: Faulkner's and Woolf's implausible speech -- The choral voice: Woolf's and Stein's democratized talk -- Conclusion: What is the dialogue doing now.
Online resource; title from PDF title page (EBSCO, viewed August 20, 2019).
Includes bibliographical references and index.
JSTOR
Keywords: American fiction -- 20th century -- History and criticism; English fiction -- 20th century -- History and criticism; Dialogue in literature; Conversation in literature; Modernism (Literature); Roman américain -- 20e siècle -- Histoire et critique; Roman anglais -- 20e siècle -- Histoire et critique; Dialogue dans la littérature.; Conversation dans la littérature.; Modernisme (Littérature); LITERARY CRITICISM / General; American fiction; Conversation in literature; Dialogue in literature; English fiction; Modernism (Literature); 1900-1999; Criticism, interpretation, etc